Differences in the Effects of Aerobic Exercise and HIIT Training on Body Fat in Adult Women - Aprillia Dhara Calista; Rahayu, Setya; hadi (Universitas Negeri Semarang, 2024)
The background to this research is the influence of the environment, lifestyle and the impact on the health of women living in rural areas. Carrying out enjoyable physical activities is necessary to improve physical health. The aim of the research was to determine the effect of aerobic exercise and body mass index on reducing body fat and physical fitness in adult women. The research method uses purposive sampling. The research sample was 60 people, consisting of 20 people in the aerobic exercise experimental group, 20 people in the HIIT experimental group and 20 people in the control group. Data was obtained through a skin fold caliper test to measure fat percentage. The resulting data was analyzed with SPSS using Two Way ANOVA. This research found that there was a difference in the effect of providing aerobic exercise and HIIT training treatment on body fat in adult women with a significance level in the Body Fat Pre Test and Post Test calculations of 0.000 and 0.006. The conclusion of this research is that there is a difference in the effect between providing aerobic exercise and HIIT training treatment. HIIT training is more likely to reduce fat than regular cardio training due to the high intensity of the training